Simulation‐as‐a‐Service: Analyzing Crowd Movements in Virtual Environments. (17th February 2021) - Usman, Muhammad; Haworth, Brandon; Faloutsos, Petros; Kapadia, Mubbasir
Abstract: At present, environment designers mostly use their intuition and experience to predictively account for how environments might support dynamic activity. The majority of Computer‐Aided Design tools only provide a static representation of space which potentially ignores the impact that an environment layout produces on its occupants and their movements. To address this, computational techniques such as crowd simulation have been developed. With few exceptions, crowd simulation frameworks are often decoupled from environment modeling tools. They usually require specific hardware/software infrastructures and expertise to be used, hindering the designers' abilities to seamlessly simulate, analyze, and incorporate movement‐centric dynamics into their design workflows. To bridge this disconnect, we devise a cross‐browser service‐based simulation analytics platform to analyze environment layouts with respect to occupancy and activity. Our platform allows users to access simulation services by uploading three‐dimensional environment models in numerous common formats, devise targeted simulation scenarios, run simulations, and instantly generate crowd‐based analytics for their designs. We conducted a case study to showcase cross‐domain applicability of our service‐based platform, and a user study to evaluate the usability of this approach. Abstract : We present a cross‐browser cloud‐based crowd analytics framework for crowd‐aware environment design. Eliminating all the hardware/software infrastructure dependencies, a single solution is proposed to bring the environment layouts from different environment modeling design tools (e.g., Autodesk Revit, SketchUp, or Rhinoceros) into an interactive crowd authoring workspace, to set up design‐specific crowd scenarios, remotely run simulations, and analyze crowd aware spatial feedback for humanŰ‐building interactions.